Analisis Penerapan ESG Reporting terhadap Nilai PT Indofood Sukses Makmur Tbk Periode 2020-2024 - Arka Nurafna Oktaviandy Wibowo; Dwi Koerniawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the implementation of ESG (Environmental, Social, and Governance) reporting on the firm value of PT Indofood Sukses Makmur Tbk during the 2020-2024 period. The main issues examined are how ESG reporting is implemented and the extent of its influence on firm value, as well as which ESG component has the most significant impact. The research method employs a quantitative approach with a causal comparative design, utilizing secondary data sourced from annual reports, sustainability reports, and market data over five years. Firm value is proxied using Tobin's Q ratio, while the level of ESG disclosure is measured based on the GRI Standards framework. Data analysis techniques use multiple linear regression by incorporating control variables including firm size, profitability (ROA), and leverage to enhance result validity. The research findings indicate that ESG reporting has a positive and significant effect on firm value with a coefficient of β = 0.018 and p < 0.001, with a model predictive capability (R²) of 87.3%. Indofood's ESG Score experienced substantial improvement from 56.3% in 2020 to 78.9% in 2024, accompanied by an increase in Tobin's Q from 0.982 to 1.523. Component-wise analysis reveals that the Social aspect provides the highest impact (β = 0.009), followed by Governance (β = 0.007) and Environmental (β = 0.006). These findings provide empirical support for stakeholder theory and resource-based view in the Indonesian emerging market context.